ON THE TRANSLATION OF MILITARY PHRASEOLOGICAL UNITS IN THE GERMAN LANGUAGE (Conferencea, 2022)
This article covers the translation and semantic analysis of military phraseological units in the German language. Military phraseological combinations are always bright and important expressions in the army subculture. Three groups of military phraseological units in the translation of the German language are given in examples. It was shown that military expressions have a different meaning in oral speech. The enrichment of military phraseology in the German language and the introduction of phraseological combinations, the pragmatic process of translation from German to Uzbek language were shown.